Pengaruh Kepuasan Pelanggan Terhadap Kepercayaan Merek, Loyalitas Merek dan Ekuitas Merek Marugame Udon - Pinkan Rosdayanti; Meylani Tuti (UNHI Press, 2023)
This study aimed to determine the effect of customer satisfaction on brand trust, brand loyalty, and brand equity. The population in this study are Marugame Udon customers in the Greater Jakarta area. The sampling technique used in this study was purposive sampling, namely customers who had made purchases more than twice so 201 people were obtained as samples. The analytical method uses a structural equation model with the help of smartPLS 3. The results show that of the seven hypotheses in this study, all of the results show acceptable results. The result is that customer satisfaction has a direct effect on brand trust. Customer satisfaction has a direct influence on customer loyalty. Customer satisfaction has an impact on brand equity. Indirect results also show that customer satisfaction has an indirect effect on brand loyalty through brand trust and customer satisfaction has an effect on brand equity through brand loyalty.